Corporate Communications in Contribution to Addressing Environmental Problems: Case Study of an Indonesian State Oil Company - Yasir, Yasir; Nurjanah, Nurjanah; Yohana, Nova; Samsir, Samsir (Information & Media, 2022)
This study aims to explain the corporate communication of state oil companies through CSR in contributing to overcoming the problems of peatland fires and coastal abrasion. This research uses a qualitative approach with case studies. Research findings indicate that Pertamina’s CSR communication targets farmer groups in dealing with peatland fires, namely establishing good relations, strengthening farmer group institutions, and connecting with other stakeholders or groups. Meanwhile, to overcome coastal abrasion, Pertamina empowers fishing groups in meetings, provides training and develops innovations to conserve mangroves. CSR communication to overcome the problem of forest fires and abrasion is carried out by developing ecotourism through community-based tourism (CBT). CSR activities are carried out with a limited area scale, so that it seems only for publication and corporate imagery. However, the company’s communication with CBT can be an effective communication model in making people aware of protecting the environment. The Peat Arboretum and Mangrove Education Center are not only tourist destinations, but also a medium of communication for environmental education for the community. Environmental communication is not only directed to the local community, school students, and youth, but also to visitors, for media coverage and discussions on social media. Corporate environmental communications must be integrated with communication channels and stakeholders to support sustainable environmental development.
Keywords: corporate communication; CSR; environmental communication; CBT; sustainable development